Knowledge and attitude towards COVID-19 among nursing students of Lalitpur (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Coronavirus disease 2019 (COVID-19) pandemic caused by a novel coronavirus mainly present with fever, dry cough, fatigue, myalgia, and dyspnea. This study was aimed to identify the knowledge and attitude toward COVID-19 among nursing students.Method: A cross-sectional analytical study was conducted to find out knowledge and attitude toward COVID-19 among nursing students of the School of Nursing and Midwifery, Patan Academy of Health Sciences, Lalitpur. Online Google form was used for data collection. The SPSS 16 version was used to analyze.Result: Out of 382 nursing students, the majority knew COVID-19, with 84.54% correct responses (6,782 out of a total 8,022). A favorable attitude toward COVID-19 was found in 209 (54.7%). There was a positive correlation between student's knowledge and attitude (r =0.10, p=0.04) and no significant association between demographic variables and attitude.Conclusion: Most (84.54%) of the nursing students surveyed knew COVID- 19 and more than half of them had a favorable attitude toward COVID.